2005
DOI: 10.1002/hup.682
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral ziprasidone: a new atypical neuroleptic for emergency treatment of psychosis in Parkinson's disease?

Abstract: This is a report on a case series of five patients with psychosis in Parkinson's disease who were treated successfully with an intramuscular injection of ziprasidone (10-20 mg) for acute agitation. No deterioration of motor function or other clinically relevant side effects were seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 13 publications
1
17
1
Order By: Relevance
“…136 Based on a case series, Oechsner and Korchounov suggested that an intramuscular injection of ziprasidone (10-20 mg) may successfully treat acute agitation in patients with psychosis in PD, without deterioration of motor function or other clinically relevant side effects. 137 Aripiprazole. No controlled studies have evaluated the use of aripiprazole in patients with PD, and preliminary data are not encouraging.…”
Section: Second-generation Antipsychotics (Serotonindopamine Antagonimentioning
confidence: 99%
“…136 Based on a case series, Oechsner and Korchounov suggested that an intramuscular injection of ziprasidone (10-20 mg) may successfully treat acute agitation in patients with psychosis in PD, without deterioration of motor function or other clinically relevant side effects. 137 Aripiprazole. No controlled studies have evaluated the use of aripiprazole in patients with PD, and preliminary data are not encouraging.…”
Section: Second-generation Antipsychotics (Serotonindopamine Antagonimentioning
confidence: 99%
“…Some authors consider ziprasidone an alternative for the emergency treatment of psychosis in PD, 44 but there is insufficient data to support its use under these conditions. 45,46 In addition, one neuroleptic malignant syndrome (NMS) has been reported with ziprasidone therapy. 47 So far, the only published case of NMS precipitated by an antipsychotic drug in a patient with PD was secondary to haloperidol.…”
Section: Management Of Comorbiditiesmentioning
confidence: 99%
“…The second open-label report [90] investigated an intramuscular preparation of ziprasidone for the emergency treatment of psychosis in PD. A total of five patients were given gluteal injections of ziprasidone 10 or 20 mg i.m.…”
Section: Ziprasidonementioning
confidence: 99%